Exposição a agroquímicos altera o funcionamento do eixo hipotálamo-hipófise-interrenal em zebrafish - Rosa, João Gabriel dos Santos da (2017)
The increase of human occupation in rural areas and the intensification of agricultural practices produces increasingly agrochemical waste up to aquatic ecosystems. Based on this, many studies are needed to clarify the mechanisms by which these substances act on non-target organisms. The present work aims to demonstrate experiments conducted to answering a few questions about the mechanisms of action of xenobiotics on aquatic organisms. Zebrafish (Danio rerio) was used as an animal model. Experiments were carried out with the following objectives: 1) evaluate whether exposure to agrichemicals has the effect to modulate the hypothalamic-pituitary-inter-renal (HPI) axis, and to answer this question was carried out an experiment of acute exposure to the organophosphorous-based insecticide methyl parathion. The fish were exposed for 96 h and genes of HPI axis components were evaluated, as well as tissue cortisol level. 2) Check whether exposure to agrochemicals cause molecular alterations in the HPI axis and by which mechanisms that occurs. 3) Check whether residues of agrichemicals in the environment interfere on environmental perception, generating behavioural changes; so an experiment was conducted in a chemotaxic chamber to verify if the presence of agrochemicals has attractive or aversive effect; and 4) Standardizing a new stressor that can be used to detect behavioral, endocrine and metabolic changes front exposure to chemical substances. Conclusions: 1) it was verified that exposure to organophosphates agrichemicals has the effect to changing the HPI axis by inhibiting expression of key genes for its activation, and 2) this change is caused by a cholinergic hyperactivity. 3) The presence of agrochemicals in water causes behavioral changes in fish exposed. 4) The new stressor model was effective to activate and modulate the HPI axis.